The Legal Vacancy of Consumer Protection in Smart Contract Execution: A Substantive Justice Approach - Totok Catur Wismo Malaicanto (JURNAL AKTA, 2026)
The Web3 digital economic transformation presents smart contracts that operate autonomously and decentralized based on the doctrine of "Code is Law." The immutable nature of these algorithms creates a legal paradox because it eliminates the obligation of good faith and cripples consumer protection, especially when virtual defaults occur, such as the practice of Rug Pull. This normative legal research aims to analyze the legal gaps in the Consumer Protection Law (UUPK), the ITE Law, and the PDP Law, and formulate a reconstruction of protection based on substantive justice. The research results show that agreements in smart contracts are vulnerable to defects of will (wilsgebrek), and the architecture that rejects refunds is a form of obfuscation by code that is null and void according to Article 18 of Law No. 8 of 1999. The immutable nature also conflicts with the right to data deletion in the Personal Data Protection Law. As crypto oversight shifts to the Financial Services Authority (OJK), problem solving demands a Fairness-by-Design approach. This research recommends mandatory Smart Contract Escrow, integrated Online Dispute Resolution (ODR), and the implementation of off-chain storage. This architectural imposition is justified by the Government's authority in Article 40A of Law No. 1 of 2024 for the sake of a fair digital ecosystem.